DEVELOPMENT OF POST-TRAUMATIC OPEN BITE IN CHILDREN AND ADULTS - Gafforov Usmon Bobonazarovich; Jasurbek Jurabekovich Ravshanov (TADQIQOTLAR, 2026)
Abstract Post-traumatic open bite is a malocclusion that may occur following injuries to the teeth, alveolar bone, or temporomandibular joint. The development and progression of post-traumatic open bite differ between children and adults due to variations in craniofacial growth, bone remodeling capacity, and adaptive mechanisms. In children, trauma may interfere with growth centers and tooth eruption patterns, often leading to progressive skeletal and dentoalveolar abnormalities. In adults, post-traumatic open bite is more commonly associated with structural damage such as condylar fractures, dentoalveolar displacement, or degenerative changes of the temporomandibular joint. Understanding the differences in pathogenesis between children and adults is essential for selecting appropriate treatment strategies. This article reviews the mechanisms through which post-traumatic open bite develops in different age groups and highlights their clinical implications.